Temporal variation in macroinvertebrate assemblage structure in the Ohio River, USA - Esther Atutey; Mark Pyron (Hydrobiologia, 2026)

Intercontinental analysis of temperate steppe stream food webs reveals consistent autochthonous support of fishes - Emily R. Arsenault; James H. Thorp; Michael J. Polito; Mario Minder; Walter K. Dodds; Flavia Tromboni; Alain Maasri; Mark Pyron; Bud Mendsaikhan; Amarbat Otgonganbat; Solongo Altangerel; Sudeep Chandra; et al. (Ecology Letters, 2022)
Quantifying the trophic basis of production for freshwater metazoa at broad spatial scales is key to understanding ecosystem function and has been a research priority for decades. However, previous lotic food web studies have been limited by geographic coverage or methodological constraints. We used compound‐specific stable carbon isotope analysis of amino acids (AAs) to estimate basal resource contributions to fish consumers in streams spanning grassland, montane and semi‐arid ecoregions of the temperate steppe biome on two continents. Across a range of stream sizes and light regimes, we found consistent trophic importance of aquatic resources. Essential AAs of heterotrophic microbial origin generally provided secondary support for fishes, while terrestrial carbon did not seem to provide significant, direct support. These findings provide strong evidence for the dominant contribution of carbon to higher‐order consumers by aquatic autochthonous resources (primarily) and heterotrophic microbial communities (secondarily) in temperate steppe streams.

Long-term trends in CPUE and relative weight of six fish species in the Wabash River, USA, prior to and following silver carp invasion - Robert Shields; Mark Pyron; Mario Minder; Luke Etchison (Hydrobiologia, 2021)

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

An assessment of the potential impacts of climate change on freshwater habitats and biota of Indiana, USA - Tomas O. Höök; Carolyn J. Foley; Paris Collingsworth; Leslie Dorworth; Brant Fisher; Jason T. Hoverman; Elizabeth LaRue; Mark Pyron; Jennifer Tank (Climatic Change, 2020)

Dietary specificity and overlap in endorheic river fishes: How do native and nonnative species compare? - Mario Minder; Emily R. Arsenault; Bolortsetseg Erdenee; Mark Pyron (Journal of Fish Biology, 2020)
The introduction of nonnative species is one of the most critical problems facing freshwater systems today. The rivers of the Great Basin (USA) have been particularly imperilled by nonnative species introductions and represent a valuable location to study the dietary trends of native and nonnative fishes in isolated, endorheic systems. We collected fish from 23 sites, spanning three Great Basin watersheds (Carson, Humboldt and Bear Rivers) and two elevation categories (upland and lowland). Only a single species (speckled dace Rhinichthys osculus ) occurred in both elevation zones. Diet item analyses of over 500 fish stomachs indicated significant dietary overlaps between native and nonnative fishes and detailed dietary selectivity for all species. This finding, along with the low species diversity observed in the region, suggests low dietary niche diversity, which could have the potential to amplify the competitive impacts of nonnatives on native species. In upland sites, nonnative trouts were the dominant invaders, while in lowland sites warm‐water nonnatives were prevalent. The management implications we recommend based on our results urge for continued monitoring of water temperature and species occurrences to predict if dietary overlaps observed in this study are likely to change in the future. Significance Statement The Great Basin is an ideal endorheic region to study dietary trends in native and nonnative fishes. These trends are important in predicting competitive interactions among fishes. By looking at the diets of fishes within this region we were able to identify multiple significant overlaps among native and nonnative fishes. These results represent a baseline for future studies in the region as well as being comparable to other regions with similar invasive/native overlaps.

Are long-term fish assemblage changes in a large US river related to the Asian Carp invasion? Test of the hostile take-over and opportunistic dispersal hypotheses - Mark Pyron; Jesse C. Becker; Kyle J. Broadway; Luke Etchison; Mario Minder; Dawn DeColibus; M. Chezem; Kevin H. Wyatt; Brent A. Murry (Aquatic Sciences, 2017)

Concordance among fish and macroinvertebrate assemblages in streams of Indiana, USA - Julie Backus-Freer; Mark Pyron (Hydrobiologia, 2015)

Effects of flow regime on growth rate in freshwater drum, Aplodinotus grunniens - Stephen J. Jacquemin; Jason C. Doll; Mark Pyron; Michael Allen; Dustin A. S. Owen (Environmental Biology of Fishes, 2015)

Does variation in morphology correspond with variation in habitat use in freshwater gastropods? - Brittany Ross; Stephen J. Jacquemin; Mark Pyron (Hydrobiologia, 2014)

Assessing changes in the Presque Isle Bay watershed fish community using a modified index of biotic integrity: before and after the elimination of combined sewer overflows - Sean D. Rafferty; Jake Lybrook; Karla M. Kaczmarek; Mark Lethaby; Robert Wellington; Mark Pyron (Environmental Monitoring and Assessment, 2013)

Cryptic phenotypic plasticity in populations of the freshwater prosobranch snail, Pleurocera canaliculata - Robert T. Dillon; Stephen J. Jacquemin; Mark Pyron (Hydrobiologia, 2013)

Fishes of Indiana streams: current and historic assemblage structure - Stephen J. Jacquemin; Mark Pyron (Hydrobiologia, 2011)

Temporal and spatial variation in the long-term functional organization of fish assemblages in a large river - Jayson Beugly; Mark Pyron (Hydrobiologia, 2010)

Temporal and spatial variation in an index of biological integrity for the middle Wabash River, Indiana - Mark Pyron; Thomas E. Lauer; David LeBlanc; David Weitzel; James R. Gammon (Hydrobiologia, 2008)

Hydrological Variation and Fish Assemblage Structure in the Middle Wabash River - Mark Pyron; Thomas E. Lauer (Hydrobiologia, 2004)

On the relative importance of pool morphology and woody debris to distributions of shrimp in a Puerto Rican headwater stream - Mark Pyron; Alan P. Covich; Robert W. Black (Hydrobiologia, 1999)

Relationships between geographical range size, body size, local abundance, and habitat breadth in North American suckers and sunfishes - Mark Pyron (Journal of Biogeography, 1999)
Summary Aim I examine the relationship between geographical range size and three variables (body size, an index of habitat breadth, and an index of local abundance) within a phylogenetic framework in North American species of suckers and sunfishes. Location North America Methods Regressions after independent contrasts of geographical range size, body size, habitat breadth, and local abundance. Results Species with large range sizes tend to be larger‐bodied, be more locally abundant, and have higher habitat breadths. Character reconstructions support the prediction that variables associated with rarity (small geographical range size, low local abundance, low niche breadth, and large body size) evolve in unison, although large body size was associated with the opposite traits in these taxa. Gaston & Blackburn (1996a) suggested using visual identification of the lower boundary of the geographical range‐body size relationship to identify extinction‐prone species; this resulted in thirteen species that are potentially extinction‐prone. Main conclusions Similar evolutionary mechanisms appear to operate on body size and other variables related to rarity, even in distantly related taxa.

Mating patterns and a test for female mate choice in Etheostoma spectabile (Pisces, Percidae) - Mark Pyron (Behavioral Ecology and Sociobiology, 1995)